The representation of mining in four Andean narrators - Plasencia Soto, Rommel (2023)
Through four novels that have mining as a central theme, it is here that exercise in literary sociology is rehearsed. Three Peruvian novels that revolve a Andean mining and Bolivian mining in a dystopian setting offer us the opportunity to tackle themes that have been recurrent in this economic activity and its impact on the communities of its hinterland. The initial trip to the mine and his foray into work in a world that is often unprecedented and alienating. The decomposition or recreation of the community or its regional environment, its characters who, like a fan, parade before us with their passions and behaviors: solidarity, suffering, degradation, ambition, or hope. Finally, some of them also introduce us (submerge) us in the underworld of sinkholes, seeing them as a metaphor in body that engulfs people, but that also grants riches. Between these levels (inside/outside), rituals unfold than have always accompanied the workers.